Pendekatan Bottom Up Budgeting dalam Penganggaran Pemerintah Daerah (Studi tentang Penganggaran Partisipatif di Komunitas Nelayan Miskin di Kawasan Pantai Prigi Kabupaten Trenggalek) - Amin, Fadillah (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2020)
Development programs dan projects funded by public budget (APBN and APBD) are frequently not inline with needs of the local fishermen. Due to this situation, there shoud be a participative forums to facilitate and accommodate interests of local communities in the formulation process of public budgeting. In the context of APBD (local government budget) budgeting, participatory events are implemented in form of Musrenbang (Discussion for Development Planning). The current article intends to describe and critically analise participatory forums of Musrenbang utilised by fishermen to participate in the process of APBD budgeting. Also, the paper aims at analising prominent constraining factors to optimise participation of local fishermen in the Musrenbang forums as manifestation of bottom-up budgeting approach. The article is written based on reseach conducted in the Regency of Trenggalek and the coastal area of Prigi. This study applies qualitative approach with analytical descriptive as its type. Data of the research are collected through interview, observation, and documentation. Furthermore, collected data got analysed in three stages include data condensation, data display, and drawing conclusion. The results demonstrate that the Musrenbang forums get executed in five phases as follows (1) village level Musrenbang; (2) sub-district level Musrenbang; (3) SKPD (local government agencies) Forum; (4) regency level Musrenbang; and (5) Pasca regency level Musrenbang. The local fishermen are mostly able to directly participate only at village level Musrenbang as Â participation at higher level Musrenbangs is commonly in form of representative participation. Quality of participation is also considerably weak because of time lack, education lack, inappropriate timing, and apathy of fishermen.